A preliminary video analysis of concussion in the National Rugby League. (September 2015) - Gardner, Andrew J.; Iverson, Grant L.; Quinn, Tanya N.; Makdissi, Michael; Levi, Christopher R.; Shultz, Sandy R.; Wright, David K.; Stanwell, Peter
Abstract Primary objective: To conduct the first video analysis of concussion in the Australian National Rugby League (NRL) and describe player and injury characteristics, situational factors and time to return to play. Research design: Descriptive, observational case series. Methods and procedures: Video analysis of 20 medically diagnosed concussions for three consenting clubs during the 2013 NRL season. Main outcome and results: Most concussions (83%) occurred during a high tackle, and all injured ball carriers were hit high. Loss of consciousness was observed in 30% of cases. Common observable signs of injury included clutching of the head, balance problems or wobbly legs and a blank or vacant state. There were no post-concussive seizures. All players with loss of consciousness were removed from play. However, only half of the total sample was removed from play and one athlete who was removed returned to play in the same match. Of the players who were removed from play, the large majority returned the following week. Illegal play accounted for 25% of all concussions. Conclusions: Video analysis may be a useful method to study the incidence, mechanism and management of concussion in sports such as Rugby League. Future studies may include larger numbers to validate this preliminary data and may also investigate other levels of play and age ranges.